PENERAPAN MEDIA PEMBELAJARAN CABRI 3D PADA KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SMK MATERI BANGUN RUANG - Sumliyah Sumliyah (Integral : Pendidikan Matematika, 2019)
Mathematics is one of the sciences that can improve conceptual understanding, reasoning, communication, and problem solving. The situation on the ground shows that these aspects have not been realized. Patterns and visualizations of geometric shapes are required to provide a good appearance so that learning objectives in understanding the concepts conveyed. Difficulties experienced by students of class X SMK XIX-3 Cirebon in learning geometry requires a solution to answer the difficulties encountered, especially in delivering the expected visual construction. Offering a solution in this research is learning with Cabri 3D media. The purpose of this study was to determine the effectiveness of the use of 3D Cabri learning media on the ability to understand mathematical concepts of students with geometrical geometry material in SMK Kartika XIX-3 Cirebon City. The sample selection in this study was done by cluster sampling technique, because the sampling method was taken by only a few classes to be used as research samples, so that in the Kartika XIX-3 Vocational School in Cirebon the sample used was Class X Nursing. The research method used in this study is the experimental method. The data obtained are then processed quantitatively by influencing test and improvement test as well as data collection techniques with tests and non tests and data analysis with inferential statistical analysis, observation guidelines and documentation.Keywords: Cabri 3D Learning Media, Understanding Mathematical Concepts